A3_5 Falling into Straw - McQuade, Gregor; Walker, Michael; Garland, Lee; Bradley, Thomas (Physics Special Topics, 2014)
The video game “Assassin’s Creed” often depicts and encourages the player to leap off tall build-ings into bales of straw/hay. This article looks into whether this is survivable, and finds the maximum height to which the depicted hay bales are safe to jump into to be about a 12-13m fall, and the max survivable fall height to be about 50m.